A study to examine the determinants of job satisfaction for professional accountants in Tanzania. (1st January 2012) - Mpeka, Rogatus L.
This study examines the level of job satisfaction and the influence of co-workers, pay, promotion, supervision, the work itself, age, and gender on the job satisfaction of Tanzanian Certified Public Accountants (Tanzanian CPAs). Results showed that most Tanzanian CPAs are satisfied with their jobs but are unhappy with pay and promotion. Results also showed that co-workers, pay, promotion, supervision, and work itself have significant influence on the job satisfaction of Tanzanian CPAs, while their age and gender have not. The implication of these results is that co-workers, pay, promotion, supervision, and the work itself are predictors of job satisfaction of Tanzanian CPAs. Therefore, Tanzanian managers must actively promote those factors in the workplace in order to foster better job performance. For future studies, the use of broader sociological and cross-cultural variables is recommended in order to identify additional variables that are vital in creating an appealing workplace for Tanzanian CPAs.